Editorial Corona Virus: A Real Phobia Or Life Threatening Alarm In Pakistan - Anwar Ali JAmali (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2019)
The phobia about corona virus reached at the borders of Pakistan. After its outbreak the whole world may be in danger, We have to sort out the possible source/vector method of spread, nature of illness. Simultaneously we to look for the strict necessary m